Fine needle aspiration biopsy cytology of phyllodes tumour and fibroadenoma: A cytomorphological study of 104 cases. Issue 11 (3rd October 2018) - Wang, Xue Yu; Mahajan, Hema; Dickinson, Nicole; Cox, Carol; Byth, Karen; Bayly, Angela; Cahill, Michael A.; Pathmanathan, Nirmala
Abstract : Background: The cytomorphological features in the distinction between phyllodes tumour (PT) and fibroadenoma (FA) on fine needle aspiration biopsy (FNAB) remains challenging because of the biphasic nature of these lesions and the rarity of PT. Methods: FNAB smears of histologically confirmed PT ( N = 26) and FA ( N = 78) cases were retrieved from a retrospective database interrogation from the Department of Cytology/Tissue Pathology, ICPMR Pathology West (Cerner Millennium) in Westmead Hospital. For each case, two smears were selected, de‐identified and independently reviewed by four observers comprising two cytologists and two cytopathologists. Cytological parameters examined included detailed evaluation of smear cellularity, epithelial and stromal components as well as the smear background. Results: The cytological features of moderate to marked stromal cellularity and stromal nuclear atypia were more evident in PT than in FA, identified by three out of four observers. The epithelial characteristics, presence of macrophages, multinucleated giant cells and blood vessels showed no statistically significant differences in the distinction between the two lesions. Conclusion: The results of this study indicate that in all of the cytological features assessed for PT and FA, no single cytological feature was found to be statistically significant in identifying PT across all observers. This reflects the overlap of cytological features seen in these lesions. FNAB cytology cannot reliably distinguish FA and PT.